P-61 How are you? the use of IPOS in clinical assessments. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Dodds, Nigel
Abstract : St Christopher's Hospice teams have now worked with the Outcome Assessment Complexity Collaborative suite of measures for a number of years. The data they generate provides a valuable tool to support clinical decision making and care. From these experiences, we have learned the IPOS tool can be used to structure and lead a patient-centred holistic assessment. Therefore, with some minor adjustments, to include questions relating to patient wishes and goals, along with a patient information leaflet, to make the tool more 'patient friendly', we now have a variation of the IPOS tool to structure all of our formal clinical assessments in our different care settings. This change supports our junior clinical staff to develop skills and competence in undertaking a palliative care holistic assessment; it also helps to standardise each patient assessment; furthermore, it enables clinicians to evaluate the impact of the previous assessment against the current one. The shift in practice has begun to provide large quantities of data, which improves our understanding of phase related symptom burden. In this presentation, there will be a focus on describing the journey we have been on, in relation to adjusting the IPOS tool, and expanding the use of the IPOS tool; and also a focus on assessment items our teams feel they struggle with, alongside data which reflects the experience of patient assessment using the St Christopher's assessment tool.